Is the Central Valley of Costa Rica a genetic isolate? - Bernal Morera; Ramiro Barrantes (Revista de Biología Tropical, 2004)
In the last decade, the Costa Rican Central Valley population (CRCV), has received considerable scientific attention, attributed in part to a particularly interesting population structure. Two different and contradictory explanations have emerged: (1) An European-Amerindian-African admixed population, with some regional genetic heterocigosity and moderate degrees of consanguinity, similar to other Latin-American populations. (2) A genetic isolate, with a recent founder effect of European origin, genetically homogeneous, with a high inter-marriage rate, and with a high degree of consanguinity. Extensive civil and religious documentation, since the settlement of the current population, allows wide genealogy and isonymy studies useful in the analysis of both hypotheses. This paper reviews temporal and spatial aspects of endogamy and consanguinity in the CRCV as a key to understand population history. The average inbreeding coefficients ?(alpha ) between 1860 and 1969 show a general decrease within time. The consanguinity in the CRCV population is not homogeneous, and it is related to a variable geographic pattern. Results indicate that the endogamy frequencies are high but in general it was not correlated with alpha ?values. The general tendency shows a consanguinity decrease in time, and from rural to urban communities, repeating the tendencies observed in other countries with the same degree of development, and follows the general Western World tendency. Few human areas or communities in the world can be considered true genetic isolates. As shown, during last century, the CRCV population has had consanguinity values that definitively do not match those of true genetic isolates. A clear knowledge of the Costa Rican population genetic structure is needed to explain the origin of genetic diseases and its implications to the health system. Rev. Biol. Trop. 52(3): 629-644. Epub 2004 Dic 15. En la última década, la población del Valle Central de Costa Rica (CRCV) ha recibido una considerable atención científica, lo que puede ser atribuido en parte a su estructura poblacional, la cual es singularmente interesante. Dos explicaciones diferentes y contradictorias han surgido: por un lado, (1) una población mezclada europea-amerindia- africana, con alguna heterogenidad genética regional y moderados grados de consanguinidad, similar a otras poblaciones de América Latina. Por otro lado, (2) un aislado genético, con un efecto fundador reciente, que es particularmente de origen europeo, genéticamente homogenea, con alta endogamia y con un alto grado de consanguinidad. La extensa documentación civil y religiosa, desde el establecimiento de la población multiétnica actual, permite hacer amplios estudios genealógicos y de isonimia útiles para el análisis de ambas hipótesis. Este trabajo tiene por objetivo revisar los aspectos temporales y espaciales de la endogamia y la consanguinidad en el Valle Central como una clave para la comprensión de la historia poblacional. Los coheficientes medios de endocruzamiento a) entre 1860 y 1969 muestran una reducción en el tiempo. La consanguinidad en el Valle Central no es homogenea, ya que un patrón de variación geográfico fue observado. Los resultados indican que la frecuencia de endogamia es alta pero en general no está correlacionada con los valores de a. La tendencia general muestra que la consanguinidad y la endogamia decrecen en el tiempo, y desde las comunidades rurales a las urbanas, repitiendo las tendencias observadas en otros países con el mismo grado de desarrollo, y siguen la tendencia general de la sociedad occidental. Pocas áreas y comunidades humanas en el mundo pueden ser consideradas aislados genéticos. Como se muestra, durante el último siglo, la población del Valle Central ha tenido valores de consanguididad que definitivamente no concuerdan con los verdaderos aislados genéticos. Un preciso conocimiento de la estructura poblacional en términos de consanguinidad es necesario debido a sus implicaciones para el sistema de salud costarricense.